Asc-Dependent and Independent Mechanisms Contribute to Restriction of Legionella Pneumophila Infection in Murine Macrophages - Amer, Amal O.; Abdelaziz, Dalia H.; Gavrilin, Mikhail A.; Akhter, Anwari; Caution, Kyle; Kotrange, Sheetal; Abu Khweek, Arwa; Abdulrahman, Basant A.; Hassan, Zeinab A.; El-Sharkawi, Fathia Z.; Bedi, Simranjit S.; Ladner, Katherine; et al. (Frontiers in Microbiology, 2011)
The apoptosis-associated speck-like protein containing a caspase recruitment domain (Asc) is an adaptor molecule that mediates inflammatory and apoptotic signals. Legionella pneumophila is an intracellular bacterium and the causative agent of Legionnaire's pneumonia. L. pneumophila is able to cause pneumonia in immuno-compromised humans but not in most inbred mice. Murine macrophages that lack the ability to activate caspase-1, such as caspase-1−/− and Nlrc4−/− allow L. pneumophila infection. This permissiveness is attributed mainly to the lack of active caspase-1 and the absence of its down stream substrates such as caspase-7. However, the role of Asc in control of L. pneumophila infection in mice is unclear. Here we show that caspase-1 is moderately activated in Asc−/− macrophages and that this limited activation is required and sufficient to restrict L. pneumophila growth. Moreover, Asc-independent activation of caspase-1 requires bacterial flagellin and is mainly detected in cellular extracts but not in culture supernatants. We also demonstrate that the depletion of Asc from permissive macrophages enhances bacterial growth by promoting L. pneumophila-mediated activation of the NF-κB pathway and decreasing caspase-3 activation. Taken together, our data demonstrate that L. pneumophila infection in murine macrophages is controlled by several mechanisms: Asc-independent activation of caspase-1 and Asc-dependent regulation of NF-κB and caspase-3 activation.